Answer:
![(3x^2+5x-8)+(5x^2-13x-5)=8x^2-8x-13](https://tex.z-dn.net/?f=%283x%5E2%2B5x-8%29%2B%285x%5E2-13x-5%29%3D8x%5E2-8x-13)
Step-by-step explanation:
The given polynomials are,
![3x^2+5x-8,5x^2-13x-5](https://tex.z-dn.net/?f=3x%5E2%2B5x-8%2C5x%5E2-13x-5)
In polynomial addition and subtraction only like terms can be added or subtracted.
So,
![=(3x^2+5x-8)+(5x^2-13x-5)](https://tex.z-dn.net/?f=%3D%283x%5E2%2B5x-8%29%2B%285x%5E2-13x-5%29)
![=3x^2+5x-8+5x^2-13x-5](https://tex.z-dn.net/?f=%3D3x%5E2%2B5x-8%2B5x%5E2-13x-5)
![=3x^2+5x^2+5x-13x-8-5](https://tex.z-dn.net/?f=%3D3x%5E2%2B5x%5E2%2B5x-13x-8-5)
![=8x^2-8x-13](https://tex.z-dn.net/?f=%3D8x%5E2-8x-13)
Answer:
c
Step-by-step explanation:
your welcome
Answer:
Yes.
Step-by-step explanation:
Lets say the first cheese has 1 hole, if you add more cheese it will have 2 holes. the more holes you have the less cheese you will have. if this continued you would eventually get less cheese.
Answer:
1
Step-by-step explanation:
Gradient (slope) = change in y / change in x
(6-5) / (3-2) = 1/1 = 1
The gradient is 1